Up | 加速度の大きさ | 作成: 2022-10-12 更新: 2022-10-12 |
ここで,はじめの2項の和は, \[ ( - \frac{v^2}{R} + R \Omega^2 )^2\ cos( P_a )^2 \\ + ( - \frac{v^2}{R} + R \Omega^2 )^2\ cos( S_a )^2\ sin( P_a )^2 \\ \ \\ \ \\ = ( - \frac{v^2}{R} + R \Omega^2 )^2\ ( cos( P_a )^2 + cos( S_a )^2\ ( 1 - cos( P_a )^2 ) ) \\ \ \\ \ \\ = ( - \frac{v^2}{R} + R \Omega^2 )^2\ ( cos( P_a )^2\ ( 1 - cos( S_a )^2 ) + cos( S_a )^2 ) \\ \ \\ \ \\ = ( - \frac{v^2}{R} + R \Omega^2 )^2\ ( cos( P_a )^2\ sin( S_a )^2 + cos( S_a )^2 ) \\ \ \\ \ \\ = ( - \frac{v^2}{R} + R \Omega^2 )^2\ ( cos( P_a )^2\ sin( S_a )^2 + ( 1 - sin( S_a )^2 ) ) \\ \ \\ \ \\ = ( - \frac{v^2}{R} + R \Omega^2 )^2\ ( 1 - sin( S_a )^2 + cos( P_a )^2\ sin( S_a )^2 ) \\ \ \\ \ \\ = ( - \frac{v^2}{R} + R \Omega^2 )^2\ ( 1 - sin( S_a )^2\ ( 1 - cos( P_a )^2 )) \\ \ \\ \ \\ = ( - \frac{v^2}{R} + R \Omega^2 )^2\ ( 1 - sin( S_a )^2\ sin( P_a )^2 ) \\ \] よって, \[ | {\bf{a}} |^2 \\ = ( - \frac{v^2}{R} + R \Omega^2 )^2\ cos( P_a )^2 \\ + ( - \frac{v^2}{R} + R \Omega^2 )^2\ cos( S_a )^2\ sin( P_a )^2 \\ + ( \frac{v^2}{R} )^2\ sin( S_a )^2\ sin( P_a )^2 \\ \ \\ \ \\ = ( - \frac{v^2}{R} + R \Omega^2 )^2\ ( 1 - sin( S_a )^2\ sin( P_a )^2 ) \\ \ \\ + ( \frac{v^2}{R} )^2\ sin( S_a )^2\ sin( P_a )^2 \\ \] |